Invasive Lobular Carcinoma With Extensive Clear Cells: A Pitfall in Diagnosis. (April 2020) - Kavesh, Mark H.; Sanchez, Daniel; Asirvatham, Jaya Ruth
Carcinomas in the breast with a predominantly clear cytoplasm are rare. In this article, we review the differential diagnosis of clear cell breast neoplasms and report a case of invasive lobular carcinoma with extensive clear cell morphology that was diagnosed as invasive ductal carcinoma, not otherwise specified, on ultrasound-guided biopsy. Lobular carcinomas with extensive clear cell change are unusual, but must be considered when evaluating a clear cell neoplasm in the breast.